2004
DOI: 10.4314/eamj.v81i4.9150
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial adenitis: role of <i>Mycobacterium bovis</i>, non-tuberculous mycobacteria, HIV infection, and risk factors in Arusha, Tanzania

Abstract: Objective: To assess risk factors and mycobacterial agents in mycobacterial adenitis. Design: Cross sectional involving comparison analysis of high-risk groups. Setting: Seven hospitals in rural and semi-rural districts of Arusha. Subjects: The study comprised of 457 patients of clinically diagnosed mycobacterial adenitis. Interventions: Biopsy materials were cultured and identification of mycobacterial isolates, and HIV infection testing were performed using standard methods. A questionnaire was used to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 11 publications
4
62
1
Order By: Relevance
“…The subject's immunogical reactivity is very important in case of mycobacterial lymphadenopathy: the severity of mycobacterial lymphoadenitis in HIV positive patients is extensively described in the literature [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The subject's immunogical reactivity is very important in case of mycobacterial lymphadenopathy: the severity of mycobacterial lymphoadenitis in HIV positive patients is extensively described in the literature [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…34 An epidemiological study from Tanzania, where these samples were taken, showed that half of the culture positive cases were caused by non-tuberculous mycobacteria and that they were as common as M. tuberculosis in granulomatous lymph adenitis. 8 In recent years, environmental mycobacterial disease have become particularly relevant to human health, due to their high prevalence in HIVcoinfected patients. 35 Considering these facts, infection with non-tuberculous mycobacteria is a public health issue, making it important to differentiate between mycobacterial species in granulomatous infections.…”
Section: Improved Diagnosis Of Tuberculous Lymphadenitis T Mustafa Et Almentioning
confidence: 99%
“…Furthermore, culture is positive in only a fraction of lymphadenitis cases. 8 Low culture positivity in extrapulmonary tuberculosis is well known and represents a general problem. This makes it problematic to use culture results as a gold standard for a test that is validated for paucibacillary tuberculosis lymphadenitis cases.…”
Section: Improved Diagnosis Of Tuberculous Lymphadenitis T Mustafa Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…2; adapted from [33,53,[77][78][79][80][81]) include the type of production system (intensive, dairy farms, use of upgraded B. taurus breeds), animal movements (herds importing animals, transhumance) and absence or inefficiency of bTB surveillance and control. Several studies have analysed bTB risks of transmission between livestock and humans [58,67,75,80,82], identifying husbandry practices (housing, mixing cattle herds with other small ruminants), food preferences (consumption of raw or soured milk) and overall health and hygienic conditions (HIV) as the main risk factors for humans (Fig. 2).…”
Section: Conceptual Model Of Btb Transmission At the Wildlife-livestomentioning
confidence: 99%